One potential hotspot SLC25A20 gene variants in Chinese patients with carnitine-acylcarnitine translocase deficiency - Li, Xiaoli; Shen, Jian (Frontiers in Pediatrics, 2022)
Background: Carnitine-acylcarnitine translocase deficiency (CACT deficiency) is a rare and life-threatening autosomal recessive disorder of mitochondrial fatty acid oxidation caused by variant of SLC25A20 gene. The most prevalent missense variant in the SLC25A20 gene in Asia was c.199-10T>G. Due to the c.199-10T>G variant, CACT deficiency is a severe phenotype. Materials and Methods: Herein, we present a neonatal case with c.199-10T>G variant in China and analyze the clinical, biochemical, and genetic aspects of 78 patients previously identified with CACT deficiency. Results: The patient presented with a series of severe metabolic crises that rapidly deteriorated and eventually died 3 days after delivery. The sequencing of the patient's genome indicated that he was homozygous for the c.199-10T>G variant. 30 patients were found to have the c.199-10T>G mutation, of which 23 were Chinese and 22 were afflicted by the c.199-10T>G splicing variation. In China, c.199-10T>G allele frequency was 82.6%. Conclusion: In CACT deficiency, early recognition and treatment are critical. Our data suggested that c.199-10T>G may be a potential hotspot SLC25A20 gene mutation in the Chinese population. Detection of single nucleotide polymorphism is possible for high-risk patients and parents in China.